2017
DOI: 10.1111/1744-7917.12453
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the Monochamus alternatus immune system

Abstract: The pine sawyer beetle, Monochamus alternatus, is regarded as a notorious forest pest in Asia, vectoring an invasive pathogenic nematode, Bursaphelenchus xylophilus, which is known to cause pine wilt disease. However, little sequence information is available for this vector beetle. This hampered the research on its immune system. Based on the transcriptome of M. alternatus, we have identified and characterized 194 immunity-related genes in M. alternatus, and compared them with homologues molecules from other s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 97 publications
0
13
0
Order By: Relevance
“…Some immune genes in the epidermis and trachea are up-regulated, and the expression level of most immune genes remains unchanged. M. alternatus maintains immune homeostasis between the two through the regulation of ROS [ 31 , 78 ]. Some researchers believe that longicorn beetles and nematodes have a symbiotic relationship [ 33 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some immune genes in the epidermis and trachea are up-regulated, and the expression level of most immune genes remains unchanged. M. alternatus maintains immune homeostasis between the two through the regulation of ROS [ 31 , 78 ]. Some researchers believe that longicorn beetles and nematodes have a symbiotic relationship [ 33 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was notable that previous studies have certified that HSPs could act as a regulator of immune response (Mehlen et al, 1996;Ravagnan et al, 2001). When blocking HSP70 with special antibody, the production of immune activity (TNF-α released from macrophages) decreased and mammalian HSPs could bind with antigenic peptides (Udono, 1993;Zhou et al, 2018). FIGURE 9 | qRT-PCR analysis of the expression levels of 13 unigenes.…”
Section: Discussionmentioning
confidence: 99%
“…PGRPs are important members of insect PRRs and play an important role in innate immunity [48,49]. Previous studies have shown that PGRP-LB1, −LB2, −LC2, −LC3 and -LD in Monochamus alternatus are likely to encode membrane proteins [50]; PGRP-SC1 of H. parallela contains a similar structure (without a signal peptide but containing a transmembrane segment), indicating that it may function on the cell membrane to recognize and trigger immune responses. Moreover, 2 of 5 key residues responsible for zinc binding and amidase catalytic activity were substituted, indicating that H. parallela PGRP-SC1 has no amidase activity and cannot cleave the bacterial peptidoglycan (PGN) [51].…”
Section: Discussionmentioning
confidence: 99%